The best technology writing 2009 - Johnson, Steven, 1968- (The Best Technology Writing, 2009)
In his Introduction to this beautifully curated collection of essays, Steven Johnson heralds the arrival of a new generation of technology writing. Whether it is Nicholas Carr worrying that Google is making us stupid, Dana Goodyear chronicling the rise of the cellphone novel, Andrew Sullivan explaining the rewards of blogging, Dalton Conley lamenting the sprawling nature of work in the information age, or Clay Shirky marveling at the 'cognitive surplus' unleashed by the decline of the TV sitcom, this new generation does not waste time speculating about the future. Its attitude seems to be: Who needs the future? The present is plenty interesting on its own. Packed with sparkling essays culled from print and online publications, The Best Technology Writing 2009 announces a fresh brand of technology journalism, deeply immersed in the fascinating complexity of digital life.